2019
DOI: 10.17576/jsm-2019-4805-11
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Choline Chloride: Urea onto Mesoporous Silica for Carbon Dioxide Capture

Abstract: A green composite adsorbent based on mesoporous silica-gel (SG) and deep eutectic solvent (DES) mixture of choline chloride-urea (ChCl:U) was synthesized as an alternative for carbon dioxide (CO 2) adsorption. The composite adsorbent was prepared by wet impregnation technique with various ChCl:U (mole ratio 1:2) content in SG at 5-15% (w/w). Fourier transform infrared attenuated total reflectance (ATR-FTIR) results showed successful impregnation of ChCl:U into SG with the presence of C=O carbonyl amide group s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Additionally, all modified adsorbents adsorbed less N2 because the deposited BMC materials (fresh adsorbents) and H2S components (exhausted adsorbents) partially filled or blocked the micropores of the adsorbents. The excess BMC material deposited on the surface of the adsorbents also resulted in low N2 adsorption, as confirmed by Ghazali et al [50], who showed that the BMC materials blocked the mesopores, preventing the N2 from diffusing inside the pore. Following the N2 adsorption experiments, the surface properties of the porous adsorbents (i.e., BET, average pore size, and pore volume) were determined as shown in Table 2.…”
Section: Surface Analysis Of Bmc Adsorbentsmentioning
confidence: 57%
“…Additionally, all modified adsorbents adsorbed less N2 because the deposited BMC materials (fresh adsorbents) and H2S components (exhausted adsorbents) partially filled or blocked the micropores of the adsorbents. The excess BMC material deposited on the surface of the adsorbents also resulted in low N2 adsorption, as confirmed by Ghazali et al [50], who showed that the BMC materials blocked the mesopores, preventing the N2 from diffusing inside the pore. Following the N2 adsorption experiments, the surface properties of the porous adsorbents (i.e., BET, average pore size, and pore volume) were determined as shown in Table 2.…”
Section: Surface Analysis Of Bmc Adsorbentsmentioning
confidence: 57%
“…Also, the interaction between DES molecules weakened, which increases the free volume and results in the diffusion of gas. Ghazali et al 25 found that the modification of mesoporous silica gel (SG) with impregnation of ChCl:urea can be considered as a promising adsorbent for CO 2 capture at atmospheric pressure and ambient temperature. However, the data of the isotherm of the NH 2 -MIL101(Cr) impregnated with the DES for the separation process are scarce.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Although DESs have attracted large attention, the investigations concerning the impregnation of solid sorbents using DES for adsorptive purification of gas streams are limited. In several works the authors described the impregnation of activated carbon with the use of choline chloride:urea (1:2 molar ratio), silica gel with choline chloride:glycerol (1:2) [34], and choline chloride:urea (1:2 molar ratio) [35] and using them to remove carbon dioxide from the gas streams.…”
Section: Introductionmentioning
confidence: 99%